THE CHEMICAL COMPOSITION AND CLASSIFICATION OF CERTAIN SYNTHETIC LAUNDRY DETERGENTS (Scientific journal of the Fergana State University, 2023)
The article discusses the chemical composition of modern synthetic detergents which are on production in present; it further provides information on the importance of assigning them product codes.